1991
DOI: 10.1159/000163666
|View full text |Cite
|
Sign up to set email alerts
|

Increased Methylation of the <i>c-fms</i>Protooncogene in Acute Myelomonocytic Leukemias

Abstract: DNA methylation provides an epigenetic information possibly involved in differentiation processes and gene regulation. In this study we investigated the methylation state of the c-fms/M-CSF receptor gene in normal human blood cells and leukemias. The methylation pattern of the c-fms gene as detected by isoschizomeric restriction analysis with Mspl/Hpall showed only slight interindividual variations in normal donors, but there were constant differences between granulocytes and monocytes from the same donor. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Hypermethylation of tumor suppressor genes and hypomethylation of oncogenes have been documented (Roberston et al, 2000). In CLL, hypomethylation has been reported at four oncogenes, BCL2, HRAS, CSF1R, and THRA1 (Browett et al 1989;Felgner et al, 1991;Hanada et al, 1993;Lipsanen et al, 1998). Each of these oncogenes showed losses of methylation that varied between samples.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of tumor suppressor genes and hypomethylation of oncogenes have been documented (Roberston et al, 2000). In CLL, hypomethylation has been reported at four oncogenes, BCL2, HRAS, CSF1R, and THRA1 (Browett et al 1989;Felgner et al, 1991;Hanada et al, 1993;Lipsanen et al, 1998). Each of these oncogenes showed losses of methylation that varied between samples.…”
Section: Discussionmentioning
confidence: 99%
“…The human CSF1R gene has been found to be aberrantly hypermethylated in leukemic cells (Felgner et al, 1991). For this reason, we evaluated the DNA methylation status of the Csf1r FIRE region in AML1-MTG16-positive cells.…”
Section: Aml1-mtg16 Induces Csf1r Histone Hypoacetylationmentioning
confidence: 99%
“…Indeed, changes in genomic methylation, either focal or global, are one of the most consistent findings in human cancers (Gama-Sosa et al, 1983; Makos et al, 1993;Vertino et al, 1993) and an epigenetic mechanism was proposed whereby such changes may contribute to neoplastic transformation by changing the expression patterns of genes involved in growth control (Antequera et al, 1990;Jones et al, 1990). For example, hypomethylation of several proto-oncogenes including c-myc (Munzel et al, 1991;Sharrard et al, 1992), ras (Bhave et al, 1988), raf (Ray et al, 1994), bcl-2 (Hanada et al, 1993), erb-Al (Lipsanen et al, 1988), and c-fins (Felgner et al, 1991) was reported in various types of cancerous tissues. In addition, expression of several tumour-suppressor genes including p16/CDKN2 (Merlo et al, 1995;Gonzalez-Zulueta et al, 1995;Herman et al, 1994), retinoblastoma (Greger et al, 1989;Sakai et al, 1991) and von Hippel Lindau gene (Herman et al, 1994) can be turned off by methylation.…”
mentioning
confidence: 99%